The Role of Premorbid IQ and Age of Onset as Useful Predictors of Clinical, Functional Outcomes, and Recovery of Individuals with a First Episode of Psychosis - Molina-García, Mariola (J Clin Med, 2021)
Background: premorbid IQ (pIQ) and age of onset are predictors of clinical severity and long-term functioning after a first episode of psychosis. However, the additive influence of these variables on clinical, functional, and recovery rates outcomes is largely unknown. Methods: we characterized 255 individuals who have experienced a first episode of psychosis in four a priori defined subgroups based on pIQ (low pIQ < 85; average pIQ ≥ 85) and age of onset (early onset < 18 years; adult onset ≥ 18 years). We conducted clinical and functional assessments at baseline and at two-year follow-up. We calculated symptom remission and recovery rates using the Positive and Negative Symptoms of Schizophrenia Schedule (PANSS) and the Global Assessment Functioning (GAF or Children-GAF). We examined clinical and functional changes with pair-wise comparisons and two-way mixed ANOVA. We built hierarchical lineal and logistic regression models to estimate the predictive value of the independent variables over functioning or recovery rates. Results: early-onset patients had more severe positive symptoms and poorer functioning than adult-onset patients. At two-year follow-up, only early-onset with low pIQ and adult-onset with average pIQ subgroups differed consistently, with the former having more negative symptoms (d = 0.59), poorer functioning (d = 0.82), lower remission (61% vs. 81.1%), and clinical recovery (34.1% vs. 62.2%). Conclusions: early-onset individuals with low pIQ may present persistent negative symptoms, lower functioning, and less recovery likelihood at two-year follow-up. Intensive cognitive and functional programs for these individuals merit testing to improve long-term recovery rates in this subgroup.